Understanding Traveler’s Experiences: A Qualitative Content Analysis Of Tourist Revisits To Massimo Italian Restaurant - Rahadiarta, I Gede Ngurah Primanda S; Pradnyaswari, Anak Agung Istri Ratih; Paulus, Eleazar Immanuel (Politeknik Pariwisata Lombok, 2025)
Introduction: This study explores the factors influencing tourists' revisits to Massimo Italian Restaurant in Sanur, Bali, Indonesia. The research aims to identify key themes that drive customer satisfaction and return visits. Methodology: The data were collected from 82 reviews written between January 1, 2023, and December 31, 2023, exploring factors influencing tourist revisit intentions at Massimo Italian Restaurant in Sanur, Bali. Qualitative research, focusing on in-depth understanding through the interpretation of textual data, allows for a comprehensive description of the phenomena observed. A purposive sampling approach was employed through a qualitative content analysis of Tripadvisor reviews. Findings: The analysis revealed seven primary themes: food quality, menu options, service quality, atmosphere, overall experience, value for money, and location. Food quality, service quality, and overall experience emerged as the top factors impacting tourists' decisions to revisit. Conclusion: This study emphasizes the critical role of service quality - including friendliness, cleanliness, attentiveness, and speed in driving customer satisfaction and fostering loyalty at Massimo Italian Restaurant. The restaurant's appealing ambience and strategic location also significantly enhance tourist revisits. These findings provide actionable insights for restaurant management and the broader hospitality industry to prioritize specific service elements, enhance guest experiences, and implement targeted improvements. Businesses can effectively boost customer retention, positive reviews, and long-term success by focusing on these key factors.